Exploring fatigue challenges and contributing factors in the South African aviation industry amidst the COVID-19 pandemic: insights from blunt-end stakeholders - Clark, Darryl Malcolm (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Background: Despite the global aviation industry's ongoing commitment to safety, crew fatigue remains a persistent and pressing issue. Within South Africa, fatigue management was primarily governed by regulations, however, there was ongoing debate about whether these regulations adequately reflected the latest scientific evidence and operational demands. This study addressed this gap by investigating perceptions about fatigue and fatigue management from management and decision-makers (blunt-end stakeholders) within the South African aviation sector. This study aimed to investigate the perceptions surrounding fatigue and fatigue management among management and decision-makers (blunt-end stakeholders) within the South African aviation sector. Specifically, it sought to contribute to ongoing research dedicated to developing a better understanding of whether, how, and why regulations pertaining to fatigue management may need to change. By exploring the perspectives of blunt-end stakeholders, the study aimed to uncover insights into the challenges and potential gaps in current regulations, with the ultimate goal of informing potential regulatory adjustments to enhance aviation safety. Methodology: A cross-sectional, qualitative exploratory design investigated perceptions about fatigue and fatigue management among blunt-end stakeholders in the South African aviation industry. Data was collected through online semi-structured interviews and written open-ended questionnaires to capture diverse perspectives. The methodology aimed to comprehensively understand fatigue-related experiences and perceptions among pilots and cabin crew, considering the unique challenges posed by the COVID-19 pandemic. Participants were selected using purposive and snowball sampling, ensuring representation from various regulatory categories and industry sectors. The study employed a thematic analysis approach to analyse data collected through online semi-structured interviews and written open-ended questionnaires. Thematic analysis facilitated the identification of key patterns and themes in the perceptions of blunt-end stakeholders within the South African aviation industry regarding fatigue and fatigue management Results: The thematic analysis of data from thirteen South African aviation industry stakeholders unveiled insights into crew fatigue challenges and regulatory concerns. Participants emphasized crew fatigue as a significant safety risk linked to entrenched crew mentalities, where instances of disregarding fatigue management protocols posed imminent safety risks. Additionally, outdated regulations were cited, hindering optimal crew rest periods and modern fatigue mitigation technologies, with discrepancies in regulatory support exacerbating challenges across operational contexts. Aviation stakeholders expressed apprehensions regarding the efficacy of existing Flight and Duty Regulations, advocating for amendments to enhance fatigue management practices. The COVID-19 pandemic further exacerbated fatigue issues, leading to shifts in crew morale, increased stress levels, and regulatory challenges, necessitating adaptive fatigue management strategies and proposed risk mitigation plans, including regulatory adjustments and enhanced stakeholder engagement. Discussion: The study investigated the intricate landscape of fatigue-related risks within the aviation industry, recognizing the systemic and context-specific nature of these challenges. It is evident from our findings, in line with previous research, that fatigue within the aviation sector is not merely an isolated issue but a multifaceted consequence of systemic factors. Our study highlights the pressing need for revisiting the current Flight and Duty Periods (FDPs) and overall fatigue management strategies to address these underlying systemic issues effectively. Unlike static safety concerns, fatigue-related risks evolve dynamically, influenced by technological advancements, industry practices, and external factors such as the ongoing COVID-19 pandemic. Our analysis elucidated the complex interplay between safety protocols, operational standards, and the well-being of crew members, emphasizing the need for a nuanced approach in mitigating fatigue-related risks. Central to our findings is the recognition of the limitations of existing regulations in adequately addressing emerging challenges associated with crew fatigue. Our study underscores the imperative of regulatory agility in safeguarding both passengers and crew members, advocating for continuous evaluation and refinement of regulatory frameworks. Specifically, there is a critical need to revisit and adapt current FDPs and fatigue management strategies to align with the systemic causes of fatigue identified in our research. Conclusion: This study contributed a comprehensive analysis of crew fatigue in South African aviation, focusing on perspectives of blunt-end stakeholders. It highlighted widespread recognition of fatigue's safety implications, exacerbated by factors like economic stressors and regulatory deficiencies, including those intensified by the COVID-19 pandemic. Participants advocated for regulatory reforms to enhance crew rest provisions and address scheduling challenges. The research underscored the need for a proactive, collaborative approach prioritizing aviation professionals' well-being. Recommendations emphasized tailored regulations, technology integration, and ongoing collaboration among stakeholders to refine fatigue management strategies and ensure industry resilience.
Keywords: Fatigue; Aircraft industry -- South Africa; COVID-19 Pandemic, 2020- Influence; Executives Attitudes; Fatigue in the workplace; Aeronautics Law and legislation -- South Africa